Dietary factors associated with metabolic syndrome in Brazilian adults - de Oliveira, Erick Prado [UNESP]; Mclellan, Katia Cristina Portero [UNESP]; Silveira, Liciana Vaz de Arruda [UNESP]; Burini, Roberto Carlos [UNESP] (Biomed Central Ltd., 2012)
Background: Metabolic Syndrome (MS) is defined as the association of numerous factors that increase cardiovascular risk and diet is one of the main factors related to increase the MS in the population. This study aimed to evaluate the association of diet on the presence of MS in an adult population sample.Methodology: 305 adults were clinically screened to participate in a lifestyle modification program. Anthropometric assessments included waist circumference (WC), body fat and calculated BMI (kg/m(2)) and muscle-mass index (MMI kg/m(2)). Dietary intake was estimated by 24 h dietary recall. Fasting blood was used for biochemical analysis. MS was diagnosed using NCEP-ATPIII (2001) criteria with adaptation for glucose (>= 100 mg/dL). Logistic regression (Odds ratio) was performed in order to determine the odds ratio for developing MS according to dietary intake.Results: An adequate intake of fruits, OR = 0.52 (CI:0.28-0.98), and an intake of more than 8 different items in the diet (variety), OR = 0.31 (CI: 0.12-0.79) showed to be a protective factor against a diagnosis of MS. Saturated fat intake greater than 10% of total caloric value represented a risk for MS diagnosis, OR = 2.0 (1.04-3.84).Conclusion: Regarding the dietary aspect, a risk factor for MS was higher intake of saturated fat, and protective factors were high diet variety and adequate fruit intake.
Keywords: Diet; Metabolic Syndrome; Diet variety; Fruit intake; Saturated fat